Histological ageing of fractures in infants: a practical algorithm for assessing infants suspected of accidental or non‐accidental injury. Issue 1 (29th April 2019) - Naqvi, Anie; Raynor, Emma; Freemont, Anthony J
Abstract : Aims: This study is the first to systematically document histological features of fractures of known age in infants (≦12 months). It has been used to develop a tabulated database specifically to guide histopathologists to age fractures in children considered to have suffered accidental or non‐accidental injury (NAI). Currently in the United Kingdom there are insufficient pathologists with experience in histological ageing of fractures to meet the medicolegal need for this examination. This study provides a practical tool that will allow those skilled paediatric and forensic pathologists currently involved in assessing infants for evidence of accidental or non‐accidental injury a basis for extending their assessment into this area of unmet need. Methods and results: One hundred and sixty‐nine fractures of known age at death were obtained from 52 anonymised infants over a period of 32 years (1985–2016 inclusive). Sections stained using haematoxylin and eosin (H&E) and Martius scarlet blue (MSB) were used to identify specific histological features and to relate them to fracture age. In 1999 the data were entered into a tabulated database for fractures accumulated between from 1985 to 1998 inclusive. Thereafter cases were added, and at 2‐yearly intervals the accumulated data were audited against the previous database and adjustments made. Conclusions: This paper describes the final data set from the 2017 audit. The study was terminated at the end of 2016, as there had been no material changes in the data set for three consecutive audits.